ANTHROPOMETRIC PARAMETERS AND INDEXES IN 9 YEAR-OLD-CHILDREN FROM R. NORTH MACEDONIA - Zafirova, Biljana; Chadikovska, Elizabeta; Trpkovska, Biljana; Stojanoska, Biljana Bojadzieva; Dodevski, Ace; Petkovska, Lidija (Journal of Morphological Sciences, 2021)
The aim of the study was the detection of sex-specific differences of anthropometric parameters and indexes that were used as indicators of growth and nutritional status in the 9-year-old-children from R.North  Macedonia.The study included 280 healthy children aged 9 (140 boys, 140 girls) from R.North Macedonia. Fourteen anthropometric parameters were measured which define longitudinal, circular and transversal measures of skeleton using standard equipment and measurement technique. The following indicators were calculated: weight-for-age (BW), height-for-age (BH), BMI, mid-upper circumference-for-age (MUAC) and skinfolds thickness (scapula SFSc and triceps SFTr)-for-age.The results have shown significant sex-specific differences in favour of boys for the height, four transversal and three circular parameters, with exception of mid-upper-arm circumference and skinfolds that were apparently higer in girls. Values of the 50 th percentile in boys were as follows: 33 kg for BW, 136 cm for BH and 17.65 kg/m 2    for BMI, 19.8 cm for MUAC and for skinfolds: SFSc 8 mm and 12 mm for SFTr.The values of these parameters in girls were: 32 kg for BW, 135cm for BH and   17.47 kg/m 2   for BMI. 20.8 cm for MUAC and for SFSc 9.8 mm and 12.8 mm for SFTr .These results can be used as criteria for the assessment of the morphological characteristics and detection of deviations in the growth and nutritional status in children aged 9.   Key words : children, anthropometry,growth, nutritional status https://doi.org/10.55302/JMS2141130z